Enhancing microbiological culture accuracy: clinical audit on the role of direct microscopy and the Bartlett scoring system in diagnostic correlation of sputum samples - Ravi, Preethika; Rao, Morubagal Ragavendra; A., Tejashree; Chitharagi, Vidyavathi B. (International Journal of Research in Medical Sciences, 2025)
Background: Lower respiratory tract infections (LRTIs) represent a significant clinical burden necessitating accurate microbiological diagnosis to guide targeted antimicrobial therapy. The quality of sputum specimens substantially influences the validity of culture results and diagnostic reliability. The Bartlett scoring system (BS) is a standardized, objective tool for assessing sputum specimen quality. However, its clinical utility in predicting culture positivity within tertiary care settings remains inadequately characterized in existing literature. Methods: A clinical audit was conducted on 212 consecutive sputum samples from patients with suspected LRTIs collected during September and October 2023 at a tertiary care center. All specimens were subjected direct microscopy examination with concurrent assessment using the Bartlett scoring system. Samples that met quality criteria (BS≥2) were processed for culture using standard microbiological techniques. Culture positivity rates were correlated with Bartlett scores to determine the association between sample quality assessment and microbiological yield. Results: Among the 212 sputum samples analyzed, specimens with higher Bartlett scores demonstrated significantly increased culture positivity rates, establishing a positive correlation between sample quality assessment and microbiological diagnostic yield. Samples classified as high-quality (BS≥2) demonstrated superior diagnostic utility compared to lower-quality specimens. The Bartlett scoring system, when applied systematically in conjunction with direct microscopy, facilitated objective specimen selection and enhanced laboratory processing efficiency. Conclusions: This audit demonstrates that the scientific utility of Bartlett scoring system serves as a valuable objective tool for assessing sputum quality and predicting culture positivity.